Responses of soil inhabiting nitrogen-cycling microbial communities to wetland degradation on the Zoige Plateau, China - Li-sha Wu; Yuan-yang Nie; Zhi-rong Yang; Jie Zhang (Journal of Mountain Science, 2016)

Using PG-Liposome-Based System to Enhance Puerarin Liver-Targeted Therapy for Alcohol-Induced Liver Disease - Ying-Zheng Zhao; Lu Zhang; Pardeep K. Gupta; Fu-Rong Tian; Kai-Li Mao; Kai-Yan Qiu; Wei Yang; Chuan-Zhu Lv; Cui-Tao Lu (AAPS PharmSciTech, 2016)

Neurofibromin Regulates Seizure Attacks in the Rat Pilocarpine-Induced Model of Epilepsy - Min Ren; Kunyi Li; Dan Wang; Jiamei Guo; Jing Li; Guang Yang; Xianghua Long; Wenjing Shen; Rong Hu; Xuefeng Wang; Kebin Zeng (Molecular Neurobiology, 2016)

MiR-449a regulates autophagy to inhibit silica-induced pulmonary fibrosis through targeting Bcl2 - Ruhui Han; Xiaoming Ji; Rong Rong; Yan Li; Wenxi Yao; Jiali Yuan; Qiuyun Wu; Jingjin Yang; Weiwen Yan; Lei Han; Baoli Zhu; Chunhui Ni (Journal of Molecular Medicine, 2016)

DBOP specifies palea development by suppressing the expansion of the margin of palea in rice - Dong-Dong Zeng; Ran Qin; Md. Alamin; Rong Liang; Cheng-Cong Yang; Xiao-Li Jin; Chun-Hai Shi (Genes & Genomics, 2016)

Responses of arbuscular mycorrhizal symbionts to contrasting environments: field evidence along a Tibetan elevation gradient - Rong Yang; Shuming Li; Xiaobu Cai; Xiaolin Li; Peter Christie; Junling Zhang; Jingping Gai (Mycorrhiza, 2016)

Microsatellite records for volume 8, issue 3 - Yan-Ling Cao; Lívia Izabela Caputo; Hongyi Cheng; Fausto Moreira da Silva Carmo; Leiliane Campos de Carvalho; Gabriel de Menezes Yazbeck; Zélia de Oliveira Teixeira; Jiaxin Fu; José Antonio Guerrero; Guibing Hu; Jun Li; Zhihua Lin; et al. (Conservation Genetics Resources, 2016)

Heat shock protein 70 inhibits cardiomyocyte necroptosis through repressing autophagy in myocardial ischemia/reperfusion injury - Xiaojuan Liu; Chao Zhang; Chi Zhang; Jingjing Li; Wanwan Guo; Daliang Yan; Chen Yang; Jianhua Zhao; Tian Xia; Yuqing Wang; Rong Xu; Xiang Wu; et al. (In Vitro Cellular & Developmental Biology - Animal, 2016)

Separation, determination and antifungal activity test of the products from a new Bacillus amyloliquefaciens - Tao Wang; Mian-Bin Wu; Zheng-Jie Chen; Jian-Pin Lin; Li-Rong Yang (Natural Product Research, 2016)

Spatio-temporal distribution of flood disasters and analysis of influencing factors in Africa - Chan-juan Li; Yuan-qing Chai; Lin-sheng Yang; Hai-rong Li (Natural Hazards, 2016)

A highly efficient grapevine mesophyll protoplast system for transient gene expression and the study of disease resistance proteins - Feng-Li Zhao; Ya-Juan Li; Yang Hu; Yu-Rong Gao; Xue-Wen Zang; Qin Ding; Yue-Jin Wang; Ying-Qiang Wen (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Comparison of skeletal muscle miRNA and mRNA profiles among three pig breeds - Xinhua Hou; Yalan Yang; Shiyun Zhu; Chaoju Hua; Rong Zhou; Yulian Mu; Zhonglin Tang; Kui Li (Molecular Genetics and Genomics, 2016)

Interaction of TIM4 and TIM3 induces T helper 1 cell apoptosis - Rong-Ti Ge; Lu Zeng; Li-Hua Mo; Ling-Zhi Xu; Huan-Ping Zhang; Hai-Qiong Yu; Min Zhang; Zhi-Gang Liu; Zhan-Ju Liu; Ping-Chang Yang (Immunologic Research, 2016)

Serological survey of avian influenza virus infection in non-avian wildlife in Xinjiang, China - Yu-Rong Wei; Xue-Yun Yang; Yuan-Guo Li; Jie Wei; Wen-Ge Ma; Zhi-Guang Ren; Hui-Ling Guo; Tie-Cheng Wang; Xiao-Yun Mi; Gulizhati Adili; Shu-Kui Miao; Ayiqiaolifan Shaha; et al. (Archives of Virology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Chemical composition, antioxidant and antimicrobial activity of the essential oil from the leaves of Macleaya cordata (Willd) R. Br. - Chun-Mei Li; Xiao-Yong Yang; Yi-Rong Zhong; Jian-Ping Yu (Natural Product Research, 2016)

Change of Polysaccharide Content and Its Relation with Nitrogen Level in Sugarcane Leaves Under Nitrogen-Fixing Bacteria Inoculation and Nitrogen Supply - Xi-Hui Liu; Hui-Ping Ou; Rong-Zhong Yang; Rong-Hua Zhang; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2016)

Large-scale comparative phosphoprotein analysis of maize seedling leaves during greening - De-Li Ning; Ke-Hui Liu; Chang-Cai Liu; Jin-Wen Liu; Chun-Rong Qian; Yang Yu; Yue-Feng Wang; Ying-Chun Wang; Bai-Chen Wang (Planta, 2016)

Association of Optic Radiation Integrity with Cortical Thickness in Children with Anisometropic Amblyopia - Shun Qi; Yun-Feng Mu; Long-Biao Cui; Rong Li; Mei Shi; Ying Liu; Jun-Qing Xu; Jian Zhang; Jian Yang; Hong Yin (Neuroscience Bulletin, 2016)

The effect of different genome and cytoplasm on meiotic pairing in maize newly synthetic polyploids - Mingjun Cheng; Mingmin Zheng; Shipeng Yang; Yang Li; Xingchun Dong; Jing Li; Rulong Sun; Huaxiong Li; Shufeng Zhou; Yuanqi Wu; Tingzhao Rong; Qilin Tang (Euphytica, 2016)
Allopolyploidization plays the special role in the evolution of many crops. Moreover, the evolution in early stage of some allopolyploidization events is predicted to be effected by nuclear-cytoplasmic interactions. Maize and teosintes are well model system for study of genetic recombination in allopolyploidization. In order to investigate the effects of genome organization and cytoplasm on genome evolution in newly synthesized allopolyploids (neoallopolyploids), a series of neoallopolyploids were produced by reciprocal crosses of maize and Zea perennis . By using dual-color genomic in situ hybridization, intra- and intergenomic meiosis pairing of these polyploids were quantified and compared with regard to its genome organization and cytoplasm background. In the four neoallopolyploids, the stability of maize genome is consistently lower than that of Z. perennis genome. Additional, the stability of maize genome is affected by genome ploidy. The cytoplasm, genome composition and their interaction do have the special role in chromosome paring and the meiosis behaviors in Zea allopolyploids vary significantly and showed non-diploidization. Z. perennis cytoplasm may give a relatively relaxed environment for maize genome.

Identification of a regulatory element responsible for salt induction of rice OsRAV2 through ex situ and in situ promoter analysis - Yong-Bo Duan; Juan Li; Rui-Ying Qin; Rong-Fang Xu; Hao Li; Ya-Chun Yang; Hui Ma; Li Li; Peng-Cheng Wei; Jian-Bo Yang (Plant Molecular Biology, 2016)

Comparison of seven colchicine-induced tetraploid clones with their original diploid clones in purple coneflower (Echinacea purpurea L.) - Rong Chen; Wei-zhen Jiang; Qing-ling Li; Xin-lian Li; Xiao-lu Chen; Yue-sheng Yang; Hong Wu (Euphytica, 2016)